Akuntabilitas Komisi Pemilihan Umum Kota Serang Dalam Mengatasi Pencatutan Data Masyarakat Secara Ilegal Melalui Sistem Informasi Partai Politik (SIPOL) Pada Pilkada Tahun 2024 - Mahpudin, Mahpudin; Ahmad Tazzul Aripin (Jurnal Silatene Sosial Humaniora, 2025)
This study examines the accountability of the General Election Commission (KPU) of Serang City in addressing the illegal misuse of citizens' personal data by political parties through the Political Party Information System (SIPOL) during the 2024 regional elections. This phenomenon reflects the weakness of personal data protection in Indonesia, resulting in violations of privacy rights and negative impacts on political rights and societal activities, particularly in the field of employment. Using a case study approach, this research explores the limited authority of the KPU of Serang City in handling this issue and its implications for electoral integrity and democracy. The findings indicate that weaknesses in the data protection system, lack of legal action against violations, and coordination barriers between the KPU and political parties are the main challenges in resolving data misuse cases. Therefore, comprehensive reforms in data governance, strengthening the authority of the KPU, and law enforcement based on the Personal Data Protection Law (UU PDP) are necessary. This study contributes to the understanding of the importance of synergy among relevant institutions in maintaining democratic integrity and public trust ahead of transparent and accountable elections.